Treatment of Steroid and Cyclosporine-Resistant Idiopathic Nephrotic Syndrome in Children. (22nd September 2011) - Nikibakhsh, A. A.; Mahmoodzadeh, H.; Karamyyar, M.; Hejazi, S.; Noroozi, M.; Macooie, A. A.
Abstract : Steroid-resistant nephrotic syndrome (SRNS) in children carries a significant risk of progression to end-stage renal failure (ESRF). We report a two-step protocol adapted in children with SRNS. Thirty-seven SRNS were treated with cyclosporine A (CyA) in association with prednisolone (alternate day) for 6 months (first-step treatment). Twelve patients (32.4%) went into complete remission, and 2 (5.4%) got partial remission. The other 23 cases who were steroid and CyA resistant entered a second-step treatment with withdrawing steroids, with CyA (5 mg/kg/day) in association with mycophenolate mofetil (MMF) 30 mg/kg/day for 6 months. Complete remission was observed in 11 cases (47.82%) and partial remission in 2 cases (8.7%). After two steps of treatment, 27/37 children went into total remission. In steroid and CyA-resistant INS, the association of MMF with CyA was able to induce remission in about half cases without relevant side effects.